Implementasi Pelaksanaan Program Guru Penggerak Terhadap Kinerja Guru di SDN Bhayangkari Kota Serang - Nur Anisa; Trian Pamungkas Alamsyah; Ahmad Syachruroji (Universitas Muhammadiyah Kuningan, 2024)
This study aims to determine the implementation of the mobilizing teacher program on teacher performance at SDN Bhayangkari Serang City, then to determine the performance of mobilizing teachers facing obstacles in leading teacher colleagues and the results of the mobilizing teacher program at SDN Bhayangkari Serang City. The method used in this study is qualitative with a descriptive qualitative type. Data collection in this study used observation, interview and documentation techniques. It was then analyzed using the Miles and Huberman model. The results of this study can reveal that from the implementation of mobilizing teachers at SDN Bhayangkari Serang City providing many changes and developments in schools through programs designed by mobilizing teachers to run a positive culture in schools with fellow teachers, mobilizing teachers also have good performance through programs that have been run and in leading and helping fellow grade 1 teachers, 2, 4 and 5 implementing the independent curriculum and the implementation of coaching as well as from the implementation of the mobilizing teacher program at SDN Bhayangkari Serang City provides many changes and developments in the school, so it can be concluded that this mobilizing teacher program is very good for school development and progress so that with the existence of this mobilizing teacher program it becomes an evaluation for the mobilizing teacher program in schools and for the program itself.